Exotic magnetization plateaus in a quasi-two-dimensional Shastry-Sutherland model - Foltin, G. R.; Manmana, S. R.; Schmidt, Kai Phillip (Physical Review B, 2014)
We find unconventional Mott insulators in a quasi-2D version of the Shastry-Sutherland model in a magnetic field. In our realization on a four-leg tube geometry, these are stabilized by correlated hopping of localized magnetic excitations. Using perturbative continuous unitary transformations (pCUTs, plus classical approximation or exact diagonalization) and the density matrix renormalisation group method (DMRG), we identify prominent magnetization plateaus at magnetizations M = 1/8, 3/16, 1/4, and 1/2. While the plateau at M = 1/4 can be understood in a semiclassical fashion in terms of diagonal stripes, the plateau at M = 1/8 displays highly entangled wheels in the transverse direction of the tube. Finally, the M = 3/16 plateau is most likely to be viewed as a classical 1/8 structure on which additional triplets are fully delocalized around the tube. The classical approximation of the effective model fails to describe all these plateau structures which benefit from correlated hopping. We relate our findings to the full 2D system, which is the underlying model for the frustrated quantum magnet SrCu(BO3)(2).